Environmental Risk in Construction Company Management - Bibliometric Analysis - Anna ŁUPICKA; Magdalena ZIĘTEK (Communications of International Proceedings, 2020)
Modern companies strive to achieve a competitive advantage in their industry, while streamlining logistics processes in such a way as to minimize costs, effort, and time. It is no different in the construction industry, the developer industry. While conducting business activity, entities make decisions in conditions of risk. This phenomenon is complex and does not have one universal definition. The risk can be considered from the point of view of both the effects and the degree of achievement of the assumed target. The authors distinguish different classifications of risk according to the area in which it arises or the factors that cause it. The type of risk, around which the article focuses, is environmental risk. The bibliometric analysis shows that environmental risk is a concept that has been present in the literature for several decades, and the trend of publications in this area is constantly growing (Web of Science - WoS). The situation is different in the case of narrowing the search to environmental risk in construction, the Web of Science database contains a small number of publications on this subject - although here too the trend is growing. This situation indicates a gap in the area under study. It should also be noted that it is the bibliometric analysis that is helpful in areas not yet recognized.
Keywords: Environmental Risk; Construction; Bibliometric Analysis; Management.